Intravenous arylsulfatase A in metachromatic leukodystrophy: a phase 1/2 study. Issue 1 (17th December 2020) - í Dali, Christine; Groeschel, Samuel; Moldovan, Mihai; Farah, Mohamed H.; Krägeloh‐Mann, Ingeborg; Wasilewski, Margaret; Li, Jing; Barton, Norman; Krarup, Christian
Abstract: Objective: Metachromatic leukodystrophy (MLD) is an autosomal recessive lysosomal storage disease caused by deficient activity of arylsulfatase A (ASA), resulting in severe motor and cognitive dysfunction. This phase 1/2 study evaluated the safety and efficacy of intravenous (IV) recombinant human ASA (rhASA; HGT‐1111, previously known as Metazym) in children with MLD. Methods: Thirteen children with MLD (symptom onset < 4 years of age) were enrolled in an open‐label, nonrandomized, dose‐escalation trial and received IV rhASA at 50, 100, or 200 U/kg body weight every 14 (± 4) days for 52 weeks (NCT00418561; NCT00633139). Eleven children continued to receive rhASA at 100 or 200 U/kg during a 24‐month extension period (NCT00681811). Outcome measures included safety observations, changes in motor and cognitive function, and changes in nerve conduction and morphometry. Results: There were no serious adverse events considered related to IV rhASA. Motor function and developmental testing scores declined during the study in all dose groups; no significant differences were observed between groups. Nerve conduction studies and morphometric analysis indicated that peripheral nerve pathology did not worsen during the study in any dose group. Interpretation: IV rhASA was generally well tolerated. There was no evidence of efficacy in preventing motor and cognitive deterioration, suggesting that IV rhASA may not cross the blood–brain barrier in therapeutic quantities. The relative stability of peripheral nerve function during the study indicates that rhASA may be beneficial if delivered to the appropriate target site and supports the development of rhASA for intrathecal administration in MLD.